Diversity and abundance of small mammals in the Serengeti kopjes, Tanzania - Timbuka , C. D.; Kabigumila , J. D. (Tanzania Journal of Science, 2021)
Diversity and abundance of small mammals in the Serengeti kopjes were studied between November 2000 and February 2002. From 22,500 trap-nights and 3,300 bucket-nights, 4,903 small mammals in 18 species, 14 genera, 6 families and 3 orders were recorded. Muridae was the most dominant family with nine species. The highest number of species was recorded in the Maasai (14), Mbuzi Mawe (13) and Seronera (12) kopjes. The least number of species recorded in the Simba, Barafu and Wogakuria kopjes, with eight species each. Species diversity was highest in the Maasai kopjes (H'=2.337) and lowest in the Wogakuria kopjes (H'=1.794), with fourteen and eight species, respectively. No significant difference in species diversity was detected between woodland and grassland kopjes, or between seasons. Distribution of species did not vary significantly between the kopjes, with most species being widespread. These include Tatera boehmi, Arvicanthis lacernatus, Graphiurus murinus and Crocidura sp. Catch rate varied from 0.519 in the Seronera kopjes to 0.103 in the Barafu kopjes. However, the difference in catch rate between the kopjes was not significant. Catch rate was significantly higher during the dry season, particularly in the grassland kopjes. The most abundant species included Mastomys anatalensis, Acomys wilsoni, G. murinus and Crocidura sp.